Kartini and Srikandi: Representation of Women in Indonesian Political Discourse through Metonymy - Muhammad Adam; Siti Hafsah; Wahyuni Wahyuni (Journal of Language and Literature, 2021)
The representation of women in politics is one of the most discussed topics in Indonesian political discourse, including political discourse in media, particularly in the Indonesian context. Two metonymies are commonly used to refer to women politicians in the Indonesian context, the first is Srikandi and the second is Kartini, both are well-known figures in Indonesian history and culture. This paper discusses the use of those two metonymies to speak about women politicians in Indonesian political discourse. The focus of the investigation is the extent of the use of the metonymy across political parties and Indonesian political level, from national to local, and the influence of the context of time to the metonymy chosen in a particular discourse. The study will also examine the characteristics that are associated with the two figures that are highlighted in metonymic use.  The study is descriptive qualitative with Conceptual Metaphor Theory – CMT as the theoretical background with ten data from news headlines that are purposively chosen for this study. The result shows that the metonymic use of both figures is extensive across parties and political levels. It is also found that the context plays important role in the use of Kartini particularly during the celebration of Kartini day on April 21; Whereas the notions of women empowerment are not reflected from all metonymic use. Thus, the text producers should not only use Kartini and Srikandi as metonymy just because of gender relatedness but should reflect more on women empowerment.